2018
DOI: 10.1101/452409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of human activities on Australian wildlife

Abstract: 2Increasing human population size and the concomitant expansion of urbanisation 3 significantly impact natural ecosystems and native fauna globally. Successful conservation 4 management relies on precise information on the factors associated with wildlife population 5 decline, which are challenging to acquire from natural populations. Wildlife Rehabilitation 6 Centres (WRC) provide a rich source of this information. However, few researchers have 7 conducted large-scale longitudinal studies, with most focussing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 76 publications
(68 reference statements)
0
7
0
2
Order By: Relevance
“…While our analysis is most directly applicable to the region where this wildlife rehabilitation facility is located, we believe this technique can be applied in other regions as well. A similar study in Australia found that car strikes, dog and cat attacks, and orphans were also top reasons for admissions, although they additionally found entanglement and disease to be highly prevalent [28].…”
Section: Overall Trendsmentioning
confidence: 94%
See 1 more Smart Citation
“…While our analysis is most directly applicable to the region where this wildlife rehabilitation facility is located, we believe this technique can be applied in other regions as well. A similar study in Australia found that car strikes, dog and cat attacks, and orphans were also top reasons for admissions, although they additionally found entanglement and disease to be highly prevalent [28].…”
Section: Overall Trendsmentioning
confidence: 94%
“…Analyses that span longer time periods could also provide insight regarding how causes of morbidity and mortality may fluctuate seasonally-valuable information for epidemiological studies of disease and human-wildlife conflicts [26,27], as well as conservation education efforts. One such study on Australian wildlife found that admissions peaked in the spring and summer during breeding seasons [28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the fate of many species could depend on accommodating their needs in urban and agricultural habitats (Ives et al, 2016). A recent assessment of data collected at the Wildlife Rehabilitation Centre in Queensland Zoo, Australia, revealed that pet cat or dog attack, car strike, and entanglement in human-placed objects represented 56.4% of the causes of submission of injured wildlife; mortality rates associated with these traumas were also high, with 61.3% of admitted animals dying from their injuries (Taylor-Brown et al, 2019). These threats may contribute to landscapes of fear, through fear arousal, altered foraging behaviour, posttraumatic stress reactions, and cumulative stress exposures resulting in chronic stress responses.…”
Section: Management Tools To Observe and Alleviate Fear And Stress Fomentioning
confidence: 99%
“…Однак ця пропозиція не здобула належної підтримки і наразі таксономічна класифікація має наступний вигляд [11,24,25 Зезекало Виктория Константиновна -асистент кафедры инфекционной патологи, гигиены, санитарии и биобезопасности, Полтавская государственная аграрная академия, ул. Сковороды, 1/3, г. Полтава, 36003, Украина, e-mail: v.zezekalo@gmail.com, ORCID ID: 0000-0003-1430-813X.…”
Section: рис 2 класифікація порядку Chlamydiales 2018 рunclassified
“…За останні роки кількість представників збільшилася настільки, що це неодноразово призводило до перегляду таксономічної класифікації порядку Chlamydiales [24,25].…”
unclassified